Neuroanatomical Correlates of Impulsive Choices and Risky Decision Making in Young Chronic Tobacco Smokers: A Voxel-Based Morphometry Study - Conti, Aldo Alberto; Baldacchino, Alexander Mario (Frontiers in Psychiatry, 2021)
Introduction: Impairments in the multifaceted neuropsychological construct of cognitive impulsivity are a main feature of chronic tobacco smokers. According to the literature, these cognitive impairments are relevant for the initiation and maintenance of the smoking behavior. However, the neuroanatomical correlates of cognitive impulsivity in chronic smokers remain under-investigated. Methods: A sample of 28 chronic smokers (mean age=28 years) not affected by polysubstance dependence and 24 matched nonsmoker controls was recruited. Voxel Based Morphometry (VBM) was employed to assess Grey Matter (GM) volume differences between smokers and nonsmokers. The relationships between GM volume and behavioral manifestations of impulsive choices (5 trial adjusting delay discounting task, ADT-5) and risky decision making (Cambridge Gambling Task, CGT) were also investigated. Results: VBM results revealed GM volume reductions in cortical and striatal brain regions of chronic smokers compared to nonsmokers. Additionally, smokers showed heightened impulsive choices (p <.01, Cohen’s f=0.50) and a riskier decision- making process (p<.01, Cohen’s f=0.40) compared to nonsmokers. GM volume reductions in the left Anterior Cingulate Cortex (ACC) correlated with impaired impulsive and risky choices, while GM volume reductions in the left Ventrolateral Prefrontal Cortex (VLPFC) and Caudate correlated with heightened impulsive choices. Reduced GM volume in the left VLPFC correlated with younger age at smoking initiation (mean=16 years). Conclusion: Smokers displayed significant GM volume reductions and related cognitive impulsivity impairments compared to nonsmoker individuals. Longitudinal studies would be required to assess whether these impairments underline neurocognitive endophenotypes or if they are a consequence of tobacco exposure on the adolescent brain.